Opposing roles for heat and heat shock proteins in macrophage functions during inflammation: a function of cell activation state? - Lee, Chen-Ting; Repasky, Elizabeth A. (Frontiers in Immunology, 2012)
Macrophages function both under normothermia and during periods of body temperature elevation (fever). Whether macrophages sense and respond to thermal signals in a manner which regulates their function in a specific manner is still not clear. In this brief review, we highlight recent studies which have analyzed the effects of mild heating on macrophage cytokine production, and summarize thermally sensitive molecular mechanisms, such as heat shock protein (HSP) expression, which have been identified. Mild, physiologically achievable, hyperthermia has been shown to have both pro- and anti-inflammatory effects on macrophage inflammatory cytokine production and overall it is not clear how hyperthermia or HSPs can exert opposing roles on macrophage function. We propose here that the stage of activation of macrophages predicts how they respond to mild heating and the specific manner in which HSPs function. Continuing research in this area is needed which will help us to better understand the immunological role of body temperature shifts. Such studies could provide a scientific basis for the use of heat in treatment of inflammatory diseases.